Very High Negative Concordance Rate of RT-PCR for SARS-CoV-2 in Nasopharyngeal Swab and Tracheo-Bronchial Aspirate in Children - Camporesi, Anna; De Silvestri, Annalisa; Diotto, Veronica; Ferrario, Stefania; Eccher, Laura; De Ferrari, Alessandra; Messina, Francesco; Pelizzo, Gloria; Mileto, Davide; Calcaterra, Valeria; Buonsenso, Danilo (Frontiers in pediatrics, 2022)
Reliable testing methods for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in children are essential to allow normal activities. Diagnosis of SARS-CoV-2 infection is currently based on real-time reverse transcriptase-polymerase chain reaction (RT-PCR) performed on nasopharyngeal (NP) swabs; concerns have been raised regarding NP swab accuracy in children to detect the virus because of potential lack of cooperation of the patients or due to general uncertainties about concordance between high and low respiratory tract specimens in children. The aim of the study (IRB approval: ST/2020/405) is to prospectively compare RT-PCR results on NP and tracheo-bronchial aspirate (TA) in children admitted to the hospital for surgery or admitted to the Pediatric Intensive Care Unit (PICU) of a tertiary children hospital in Milano, Italy, during a peak of COVID-19 infections in the city. A total of 385 patients were enrolled in the study: 364 from surgical theater and 21 from PICU. Two patients (0.5%) tested positive on TA and were negative on NP; both cases occurred in November 2020, during a peak of infection in the city. Specificity of NP swab was.995 (95% CI: 0.980–0.999). Two patients with positive NP swabs tested negative on TA.